PERANAN ANGGOTA TERHADAP KELOMPOK TANI â€œELDORADOâ€ PADA USA-HATANI PADI SAWAH DI DESA TOUNELET KECAMATAN SONDER (The Role of Its Membersin â€œEldoradoâ€ Rice Farmer Group in Tounelet Village, District of Sonder) - Beatrix H. Tambuwun; Melsje J. Memah; Vicky R. B. Moniaga (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2021)
This research is intended to determine the Role of Members of the "Eldorado" farmer group in Rice Farming in Tounelet Village, Sonder District. Research was conducted from November 2020 - Januari 2021. Four people out from from 16 members of the farmer group were taken as respondents. A descriptive method was applied.Â  Data were presented in tabular forms andÂ  then interpreted to draw conclusion. The research findings showed that the Role of the members of the Eldorado farmer group was predominantly falled into the high category.